Integrated Rail System and EV Parking Lot Operation With Regenerative Braking Energy, Energy Storage System and PV Availability - Cicek, Alper; Sengor, Ibrahim; Guner, Sitki; Karakus, Furkan; Erenoglu, Ayse Kubra; Erdinc, Ozan; Shafie-Khah, Miadreza; Catalao, Joao P. S. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
A significant advancement regarding the electrification of transportation has occurred in recent years due to technological developments, environmental concerns, and geopolitical issues in the energy areas all over the world. In this study, a new concept for the integration of rail-based public transportation systems with electric vehicle (EV) parking lots operated by a park and ride strategy is propounded, including also renewable resources based energy production. In the proposed structure, the charging power demand of the EV parking lot is supplied by different charging strategies considering the existing unused energy infrastructure capacity and the regenerative braking energy of the railway system, altogether. Here, the design of a photovoltaic (PV) based carport type renewable energy production unit is also realized in the existing local parking area. The development of an optimal energy management system to effectively manage these inputs is realized and the uncertainties pertaining to EVs' demand are also taken into account. To demonstrate its efficacy, the concept is tested considering a bench of case studies and comprehensive results are obtained.
Keywords: Rail transportation; Transformers; Production; Automobiles; Renewable energy sources; Power demand; Charging stations; electric vehicles; energy management; railway systems; regenerative braking energy; renewable energy resources; MANAGEMENT; MOBILITY; Engineering